Secondary metabolite profiling of Aristolochia gigantea seeds extract by GC−EI/MS and NMR analysis - Anjos De Stefano Escaliante, Gabriela [UNESP]; Luiza Cunha, Camila [UNESP]; Rodrigues Nascimento, Isabele [UNESP] (Taylor & Francis, 2025)
Aristolochia gigantea (Aristolochiaceae), commonly known as the Brazilian Dutchman’s pipe, is cultivated globally as an ornamental vine, admired for the unique shape of its large flowers. In our ongoing research into the chemical composition of A. gigantea, the ethanol extract from its seeds was fractionated using chromatographic techniques, resulting in the isolation and identification of allantoin, along with the lignans kobusin, eudesmin, and methylarctigenin. The fractions were further analysed by NMR and GC − EI/MS, employing a molecular networking approach and retention index comparison, which led to the annotation of four sterols, eleven aliphatic alcohols, one saturated fatty acid, two unsaturated fatty acids, ten esters of saturated fatty acids, ten esters of unsaturated fatty acids, and one lactone.
Keywords: Aristolochia gigantea; GNPS; lignan; molecular networking; seed